PlayTogether: Playing Games across Multiple Interactive Tabletops - Wilson, Andy; Robbins, Daniel C. (IUI Workshop on Tangible Play: Research and Design for Tangible and Tabletop Games, 2007)
Playing games together can be surprisingly difficult – people have limited free time and are tending to live live farther away from friends and family. We introduce PlayTogether, a system that lets people play typical (and as-yet-unimagined) board games together even when they are far away from each other. We have adapted the PlayAnywhere tabletop system so that multiple remotely located people can engage in game-play. PlayTogether enhances the play experience by exchanging carefully composited video of remote players’ hands and real game pieces. The video that is transmitted mimics a player’s viewpoint via careful camera location. Because PlayTogether’s camera senses in the infrared, it is easy to distinguish between objects in the camera’s view and projected imagery. These capabilities create an interesting and engaging way to blend the virtual and real in multi-player gaming.